Faktor Penyakit Komorbid dan Riwayat Kontak Erat terhadap Kejadian COVID-19 di Surabaya Selatan - Jessie Angeline Nathasya; Septa Ria Agina Perangin Angin; Fariani Syahrul; Ratna Dwi Wulandari (Universitas Airlangga, 2023)
Background: Comorbid diseases are one of the risk factors that can worsen the condition of COVID-19 patients. Patients with confirmed COVID-19 with comorbid diseases need special care, therefore, it is necessary to receive treatment in a hospital. The human-to-human transmission rate of SARS COV-2 is very fast and easy. Close contact with confirmed cases of COVID-19 is very possible for transmission to occur because this virus can be easily spread through droplet sparks. Cases and death rates from Covid-19 continue to grow over time. On March 7, 2021, the highest proportion of confirmed cases of covid-19 in Surabaya was in South Surabaya and East Surabaya, the resulting proportion was 0.82%. South Surabaya has a higher severity than East Surabaya (death rate from COVID-19 = 6%). Objectives: This study aims to analyze the magnitude of risk factors for comorbid diseases and close contact history the incidence of COVID-19 in South Surabaya. The benefit of this research is to assist the government in making policies to handle the surge in COVID-19 cases in South Surabaya. Methods: This study uses the type of observational analytical research with cross sectional design and sampling techniques used are participatory sampling. The number of samples is calculated using the formula Murti (1997). The sample size was 89. Statistical analysis used Prevalence Ratio (PR). Results: Respondents with negative PCR swab test result is 60,7% and positive result is 39,3%. Respondent with comorbid disease only as many as 17 respondents with the majority having comorbid hypertension. Respondent with close contact history is 71,9%. Comorbid diseases have a risk of covid-19 incidence in South Surabaya with PR = 2.06 while close contact history, PR = 2.34. Conclusions: Comorbid diseases have a risk of 2.06 times with the incidence of COVID-19 in South Surabaya. As for close contact history, it has a risk of 2.34 times with the incidence of COVID-19 in South Surabaya. The close contact history factor has a higher probability value in incidence of COVID-19 in South Surabaya. The Surabaya city government can pay special attention to people with comorbid diseases and increase tracing of close contacts with COVID-19 patients.